Campaniforme no Norte de Portugal. Perspectivas interpretativas instigadas pela leitura de dados recentes - Sanches, Maria de Jesus; Barbosa, Maria Helena (Portvgalia : Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da FLUP, 2018)
This paper focuses on the contexts with bell-beaker ceramics of the North of Portugal / Douro basin and compares them with neighboring regions, particularly with Galicia, covering the end the whole Northwest of the Iberian Peninsula. After presenting a brief historiography of the studies in this region, it critically approaches the set of archaeological sites, emphasizing those with absolute dates and well preserved stratigraphies. Among them, it stands out the Crasto de Palheiros monumental enclosure because its bell-beaker ceramics have never been completely published and it is the archaeological site in northern Portugal that has yielded the largest number of sherds and vessels. Also, the quality of information obtained in the excavation allows to relate the campaniform contexts with the biography of the site. The paper also outlines the synthesis of this region, in relation to neighboring Galicia. In the discussion, it concludes the long duration of use of bell-beaker ceramics (from 2800/2700 to 1900/1800 BC) and, insofar as it also develops formal and decorative stylistics, raises interpretative hypotheses concerning the plurality of social functions that, in this long chronology, classical bell-beaker ceramics and local styles would have played in each local or regional context.